Converting a residue from an edible source (Ceratonia siliqua L.) into a bio-oil. Issue 2 (April 2019) - Mateus, Maria Margarida; Gaspar, Daniela; Matos, Sandro; Rego, Andreia; Motta, Carla; Castanheira, Isabel; Bordado, João Moura; Galhano dos Santos, Rui
Abstract: The direct liquefaction of the wastes from carob pod processing industry leaded to a biooil with 88% of conversion, further water extraction afforded two extracts that can be used, e.g., as alternatives to the synthetic antioxidants. The hydroxyl number, as well as acid value, were screened for the reaction crude and both extracts. The organic extract, despite its high concentration of phenolic compounds (19.3 g GA eq/mg extrc), proved to be less antioxidant (1.05 μL/mL) than the aqueous congener (total phenolic content, 0.92 GA eq/mg extrc; antioxidant activity, 1.19 μL/mL). Nevertheless, both extracts have proved to be more active than BHT. The composition of the aqueous extract regarding its sugar's content was also studied, revealing the presence of glucose, fructose, and sucrose. The higher heating value, estimated by Dulong's formula, along with the analysis of van Krevelen diagram indicate that the organic extract can be potentially used as a fuel, an additive or as components in fuel blends. Briefly, this work proves that carob waste can be valued as an antioxidant additive, as fuels or even as a sugar platform.